Medical and non-medical direct costs of cancers in patients hospitalized in Imam Khomeini cancer institution - 2010 - M Bazyar; A pourreza; Iraj harirchi; F Akbari; M Mahmoudi (Tehran University of Medical Sciences, 2012)
Background: With more than 12 million new cases of cancers and nearly 7.6 million deaths all around the world in 2007, cancer currently is the third leading cause of death in the world. This study was conducted to determine medical and non-medical direct costs of cancer patients' hospitalized in the cancer institute affiliated with Imam Khomeini hospital. Materials and Methods: This was a cross-sectional study. All patients over 18 years old with kind of head, neck, and stomach cancers that undertaken of oncology treatments in the cancer institute which affiliated " Imam Khomeini Hospital". Initially eligible patients invited to participate in this study. The data was collected through structured interviews with patients and or their carers. The data, then, was analyzed by SPSS software. Results: The average medical and non-medical direct out-of-pocket costs during primary treatment were 2,609,000 and 245,000 Tomans per patient, respectively. Furthermore, the direct average of medical costs for patients who lived in Tehran and other cities were 3,313,000 and 1,870,000 Tomans while the direct average of non-medical costs for patients who lived in Tehran and other cities were 136,000 and 360,000 Tomans, respectively. Conclusion: The new policies for costs coverage related to cancer patients', particularly the medical insurance organizations, financial supports from finance intuits like as banks or charity organizations, appropriate distribution of cancer's centers or providing accommodation to cancer patients who are referred from the remote sites in other cities, and also achieving the equities in health sectors could be reduced the financial costs of cancer patients and might be helped them to manage of cancers efficiently and effectively